Idiopathic Chylothorax in Infants - Is Octreotide Alone Enough? - Maralihalli, MB; Matti, MR; Joshi, SN; Annigeri, VM (Journal of Nepal Paediatric Society, 2015)
Five month old female baby presented to us for evaluation of asymptomatic right sided pleural effusion. Pleural fluid analysis revealed it as chylous effusion. Radiological investigations revealed gross right side pleural effusion with partial collapse of right lung. After investigations, diagnosis of asymptomatic idiopathic chylothorax was made. Baby was treated with Inj. Octreotide alone. Pleural drain was not placed. After three doses of Octreotide, there was complete clearance of pleural effusion. J Nepal Paediatr Soc 2015;35(1):64-66